2016
DOI: 10.1038/tp.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma predicts antidepressant response in adults with major depression: data from the randomized international study to predict optimized treatment for depression

Abstract: Few reliable predictors indicate which depressed individuals respond to antidepressants. Several studies suggest that a history of early-life trauma predicts poorer response to antidepressant therapy but results are variable and limited in adults. The major goal of the present study was to evaluate the role of early-life trauma in predicting acute response outcomes to antidepressants in a large sample of well-characterized patients with major depressive disorder (MDD). The international Study to Predict Optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
134
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 44 publications
19
134
1
3
Order By: Relevance
“…For those with MDD, a recent study in USA found that nearly 62.5% patients reported more than two traumatic events 27 . In our study, we found 47.5% patients of MDD There are some limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For those with MDD, a recent study in USA found that nearly 62.5% patients reported more than two traumatic events 27 . In our study, we found 47.5% patients of MDD There are some limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with depression, prior childhood trauma was associated with reduced efficacy of both pharmacotherapy and psychological therapies and longer time to remission. [216] …”
Section: Contributing Factorsmentioning
confidence: 99%
“…Engagement of the stress system can fundamentally change amygdala structure and function, especially as a result of ELS (2,(9)(10)(11). Moreover, the amygdala is likely a component of the neural circuit involved in antidepressant action (12,13), and the antidepressant response is modified by prior stress exposure (10,14). Despite these mechanistic foundations, amygdala-stress interactions have not been investigated as a prognostic biobehavioral therapeutic target for depression.…”
mentioning
confidence: 99%